Phenological growth stages of quinoa (Chenopodium quinoa) based on the BBCH scale. (31st March 2017) - Sosa‐Zuniga, V.; Brito, V.; Fuentes, F.; Steinfort, U.
Abstract: Quinoa ( Chenopodium quinoa ) is a pseudocereal native from the Andean region of South America that has increased in importance worldwide. Quinoa is now considered an alternative to traditional crops in a climate change scenario, considering its ability to adapt to marginal soils, droughts and frosts. Despite the interesting agronomic and nutritional features of this crop, research into quinoa is characterised by individual attempts to define its phenological stages without an international consensus. A unique criterion to quantify the phenology of quinoa could become a useful tool for researchers and plant breeders in future work by standardising this information for international cooperation. In this article, a proposed scale of the phenological growth stages of quinoa based on the BBCH coding system (Biologische Bundesanstalt Bundessortenamt und CHemische Industrie) was developed. Growth stages were described utilising the decimal code of the BBCH system, and figures were included for the most representative stages.